What variables determine sprint performance in young athletes? - Alvesa, P. L.; Castro, P. H. C.; Freitas, J. V.; De-Oliveira, F.-R.; Lima, J. R. P.; Cruz, R. (Science & Sports, 2021)
Objectives: To identify sprint performance determinants in young athletes in the field in both sexes. Equipment and methods: Two hundred and fourteen track and field athletes, ages between 13 and 15 years old, were divided into validation group (VG) (n = 163) and cross-validation group (CVG) (n = 51). The participants were submitted to biological maturity evaluation, anthropometry, vertical jump, 60-m sprint, and running anaerobic sprint test (RAST). Results: The multiple regression analysis selected the variables leg length, vertical jump, RAST total time (RASTtt) and fatigue index for both groups, determined 95.5% and 76.9% of sprint performance on boys and girls, respectively. To confirm our results, we performed a cross-validation on the linear regression, which showed that the measured and predicted sprint performances in CVG were not significantly different (P > 0.05). In addition, the study demonstrated that biological maturity is associated with all variables of the model (P < 0.05). Conclusion: The variables leg length, vertical jump, RASTtt and fatigue index explain in different proportions sprint performance in young boys and girls athletes. In addition, this study add to knowledge of researchers and coachers, indicating which variables should be part of the training program of young athletes sprint runners.